1963
DOI: 10.1037/h0047169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of group size.

Abstract: This paper reviews 31 empirical studies of small groups in which the major independent variable, group size, was related to several classes of dependent variables: group performance, distribution of participation, the nature of interaction, group organization, member performance, conformity and consensus, and member satisfaction. Many of these variables were found to be significantly affected by group size, but methodological shortcomings characterizing this group of studies preclude the assertion of broad gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1
3

Year Published

1970
1970
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(108 citation statements)
references
References 33 publications
4
100
1
3
Order By: Relevance
“…The findings suggested that the larger stations were more compatible and effective than smaller stations. Such results do not conform to those reported in other studies where small group size has consistently correlated with member perceptions of g-eater cchesiveness or compatibility (Viteles, 1953;Seashore, 1954;Thomas and Fink, 1963), and to a lesser degree small size has been seen as positively related to group achievement (McGrath and Altman, 1966).…”
contrasting
confidence: 54%
“…The findings suggested that the larger stations were more compatible and effective than smaller stations. Such results do not conform to those reported in other studies where small group size has consistently correlated with member perceptions of g-eater cchesiveness or compatibility (Viteles, 1953;Seashore, 1954;Thomas and Fink, 1963), and to a lesser degree small size has been seen as positively related to group achievement (McGrath and Altman, 1966).…”
contrasting
confidence: 54%
“…For example, ample research has documented the effect of size and resources on group process and outcomes (Gladstein, 1984;Hackman, 1982;Thomas & Fink, 1963). In addition, studies of research and development teams have documented the impact of task and product characteristics on performance (c.f.…”
Section: Complex Relationshipsmentioning
confidence: 99%
“…Whatever the underlying processes may be, it is clear that close attention must be given to the effect of group size in learning experiments, especially when the study time is self-paced. Unexpected effects of group size were warned against 20 years ago by Thomas and Fink (1963), but researchers do not seem to have paid much attention to them.…”
Section: Discussionmentioning
confidence: 99%